The ontogenesis of the vertebral column of Xenopus laevis (Daudin), with special reference to the segmentation of the metotic region of the skull - Smit, A. L (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1952.